Efektivitas Terapi Akupressure dan Teknik Efflurage pada Ibu Bersalin Kala I Di Puskesmas Bontobangun - Risnawati; Andi Nurlaily; Rusnawati (Comprehensive Health Care, 2023)
Labor is a physiological process and is an amazing incident for a mother and family. Most ( 90%) deliveries are accompanied by pain. Labor pain start occurs during the 1st stage of labor in the latent phase. The longer the pain is felt will increase strong, and the peak pain occurs in active phases, where the opening completes up to 10 cm. Intensity is painful during labor and will influence the condition of the psychological mother, the childbirth process, and the welfare fetus. this research aims To know effective therapy acupressure and techniques effleurage For reducing painful contractions in the mother giving birth during the I Active Phase. The method used in the study This is analytic with type design study quasi-experimental. Population in study This is the Mother’s third trimester of pregnancy at the health center Bontobangun. Deep sample study This is Mother giving birth during phase I activities. Data collection uses primary data, giving therapy done in a manner directly to the respondent with gift intervention from acupressure therapy at point BL60 and regional effleurage stomach and lumbar as well as the sacrum. results study can conclude that there is a difference average scale pain between a mother who gets effleurage therapy with acupressure therapy